2020
DOI: 10.1177/1938965520951751
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Application of Composite-Based Structural Equation Modeling in Hospitality Research With Empirical Example

Abstract: Partial least squares path modeling (PLS-PM) and generalized structured component analysis (GSCA) are two key estimators derived from a full-fledged composite-based structural equation modeling (SEM). The analyses of PLS-PM and GSCA have been recently extended to mimic factor-based SEM, and the extended approaches are called PLSC and GSCAM, respectively. Simulation studies have confirmed that the relative performance of PLS-PM is comparable with that of GSCA. Similarly, GSCAM, PLSC, and the traditional factor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 38 publications
1
32
0
1
Order By: Relevance
“…The method was introduced by Hwang and Takane (2004) in the psychometric literature. Applications can be found in several fields not limited to marketing (Hwang et al, 2010), hospitality (Manosuthi et al, 2021), healthcare (Avkiran, 2018) and biological sciences (Jung et al, 2016;Romdhani et al, 2015). GSCA is a global optimization method based on the least-squares criterion for parameter estimation.…”
Section: Methodsmentioning
confidence: 99%
“…The method was introduced by Hwang and Takane (2004) in the psychometric literature. Applications can be found in several fields not limited to marketing (Hwang et al, 2010), hospitality (Manosuthi et al, 2021), healthcare (Avkiran, 2018) and biological sciences (Jung et al, 2016;Romdhani et al, 2015). GSCA is a global optimization method based on the least-squares criterion for parameter estimation.…”
Section: Methodsmentioning
confidence: 99%
“…Following the recommendation of Manosuthi et al (2021), all AVE values should be greater than 0.5, and the Dijkstra–Henseler (ρa) indicator should be above 0.7 but lower than 0.95. Furthermore, the estimated weight scores must be positive, and the 95% of bias corrected confidence interval must not include zero.…”
Section: Resultsmentioning
confidence: 99%
“…In prior simulation and empirical studies, the relative performance of GSCA is marginally greater than PLS in terms of statistical power (Cho and Choi, 2020). Parameters estimated on the basis of a GSCA algorithm can also be considered full information and tends to estimate parameters more accurately than PLS (Manosuthi et al , 2021). Hence, GSCA was chosen as the main estimator in this research.…”
Section: Methodsmentioning
confidence: 99%
“…In assessing composite‐based SEM, Benitez et al (2020) classified measurement model constructs as design and behavioural concepts. In this research, the nature of the measurement indicators was considered, and the newly identified LC tourism components and the tourists' satisfaction, involvement and LC behaviours were categorised as design constructs measured by the composite‐formative model, whereas immunity was measured by the common factor reflected by the behavioural concept (Manosuthi et al, 2021).…”
Section: Methodsmentioning
confidence: 99%